2016
DOI: 10.1103/physrevc.93.031302
|View full text |Cite
|
Sign up to set email alerts
|

Particle-rotor versus particle-vibration features ingfactors ofCd111andCd113

Abstract: The emergence and evolution of collective excitations in complex nuclei remains a central problem in the quest to understand the nuclear many-body problem. Nuclear quadrupole collectivity is usually investigated via electric quadrupole observables. Here, however, we measure the g factors of low-excitation states in 111 Cd and 113 Cd and show that they are sensitive to the nature of the collectivity in these nuclei in ways that the electric quadrupole observables are not. The particle-vibration model, which as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 19 publications
6
24
0
Order By: Relevance
“…It follows an earlier study in which it was shown that for both 111 Cd and 113 Cd, the g factors of the 1/2 + ground-states, and the strongly Coulombexcited low-lying 3/2 + and 5/2 + levels are consistent with a particle-plus-rotor description whereas the signs of the g factors of the 5/2 + states are incompatible with the particle-vibrational model [23]. Contrasting with this observation, a 3/2 + state at 681 keV in 113 Cd was excited with sufficient intensity to determine its g factor, giving g = +1.4(4) [23]. Such a large g factor in a collective odd-N nuclide is difficult to explain unless it is associated with the coupling of an odd-neutron in the νs 1/2 orbit to a spherical 2 + core excitation.…”
Section: Introductionsupporting
confidence: 87%
See 2 more Smart Citations
“…It follows an earlier study in which it was shown that for both 111 Cd and 113 Cd, the g factors of the 1/2 + ground-states, and the strongly Coulombexcited low-lying 3/2 + and 5/2 + levels are consistent with a particle-plus-rotor description whereas the signs of the g factors of the 5/2 + states are incompatible with the particle-vibrational model [23]. Contrasting with this observation, a 3/2 + state at 681 keV in 113 Cd was excited with sufficient intensity to determine its g factor, giving g = +1.4(4) [23]. Such a large g factor in a collective odd-N nuclide is difficult to explain unless it is associated with the coupling of an odd-neutron in the νs 1/2 orbit to a spherical 2 + core excitation.…”
Section: Introductionsupporting
confidence: 87%
“…This nucleus lies between 110 Cd and 112 Cd, both of which have been considered textbook examples of vibrational nuclei [1,22]. It follows an earlier study in which it was shown that for both 111 Cd and 113 Cd, the g factors of the 1/2 + ground-states, and the strongly Coulombexcited low-lying 3/2 + and 5/2 + levels are consistent with a particle-plus-rotor description whereas the signs of the g factors of the 5/2 + states are incompatible with the particle-vibrational model [23]. Contrasting with this observation, a 3/2 + state at 681 keV in 113 Cd was excited with sufficient intensity to determine its g factor, giving g = +1.4(4) [23].…”
Section: Introductionsupporting
confidence: 69%
See 1 more Smart Citation
“…They can be compared to the Cd isotopes (Z=48) with two proton holes, which have been more extensively studied. There is an ongoing discussion on the nature of the collectivity that, in the Cd isotopes, is traditionally associated with anharmonic vibrations [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…However, experiments on Cd isotopes carried out by Garrett [1,2], Ekström [3] and Stuchbery [4], among others, suggest a more complex nuclear structure for some Cd nuclei, including the existence of deformation with consequent rotational motion.…”
Section: Introductionmentioning
confidence: 99%